Prevalence and antifungal susceptibility of Candida parapsilosis complex isolates collected from oral cavities of HIV-infected individuals - Moris, D. V. [UNESP]; Melhem, M. S. C.; Martins, M. A.; Souza, L. R. [UNESP]; Kacew, S.; Szeszs, M. W.; Carvalho, L. R. [UNESP]; Pimenta-Rodrigues, M. V. [UNESP]; Berghs, H. A. M.; Mendes, Rinaldo Poncio [UNESP] (Soc General Microbiology, 2012)
At present, few data are available on the prevalence and antifungal susceptibility of Candida parapsilosis complex isolates from HIV-infected individuals. The C. parapsilosis complex comprises three species, C. parapsilosis sensu stricto, C. metapsilosis and C. orthopsilosis. Fifteen of 318 Candida isolates were identified as members of the C. parapsilosis complex by PCR and restriction fragment length polymorphism (RFLP). The prevalence of C. parapsilosis complex isolates was 4.7 %, 2.2 % being identified as C. parapsilosis sensu stricto and 2.5% as C. metapsilosis, while no C. orthopsilosis was isolated. This is believed to be the first study that has identified isolates of C. metapsilosis obtained from the oral cavity of HIV-infected individuals. Antifungal susceptibility tests indicated that all the isolates were susceptible to amphotericin B (AMB), fluconazole (FLC), ketoconazole (KTC), itraconazole (ITC), voriconazole (VRC) and caspofungin (CASPO). Although isolates of C. parapsilosis sensu stricto and C. metapsilosis were susceptible to FLC, isolates of C. metapsilosis showed a tendency for higher MICs (>= 1.0 mu g ml(-1)). Based upon the frequency of candidiasis and the fact that certain isolates of the C. parapsilosis complex respond differently to FLC therapy, our data may be of therapeutic relevance with respect to susceptibility and potential resistance to specific antifungal agents. Our data suggest that C. metapsilosis can be a human commensal; its importance as a pathogen has yet to be confirmed.